Application of Quantitative PCR in the Diagnosis and Evaluating Treatment Efficacy of Leishmaniasis - Wu, Yun; Tian, Xiaojun; Song, Nan; Huang, Minjun; Wu, Zhaoyong; Li, Shaogang; Waterfield, Nicholas R.; Zhan, Bin; Wang, Lei; Yang, Guowei (Frontiers in Cellular and Infection Microbiology, 2020)
Leishmaniasis is still a serious neglected tropical disease that may cause death in infected individuals. At present, the clinical diagnosis and treatment monitoring still rely on parasitological culture and microscopy that needs experienced technicians. The low sensitivity and inconvenience of microscopic examination could cause misdiagnosis and relapse of leishmaniasis. There is an urgent need for developing a sensitive and easily operated diagnostic method for the diagnosis and disease management of leishmaniasis. Thus, a quantitative real-time PCR (qPCR) based on the conversed regions of kinetoplast minicircle DNA (mkDNA) of Leishmania spp. was developed to detect different species of Leishmania. The designed mkDNA-based qPCR was able to detect as low as one copy of Leishmania mkDNA or DNA from single parasite. It also detected Pan-Leishmania protozoa including Leishmania donovani, Leishmania infantum and Leishmania major without cross-reaction with other pathogen DNAs available in our lab. This method was clinically applied to quantitatively detect skin lesion samples from 20 cutaneous leishmaniasis (CL) and bone marrow and/or PBMC samples from 30 current and cured visceral leishmaniasis (VL) patients, and blood samples from 11 patients with other infections and 5 normal donors as well. Total 20 skin lesion samples from current CL patients and 20 bone marrow and/or PBMC samples from current VL patients were all detected as positive with qPCR without cross-reaction with samples from patients with malaria, brucellosis and dengue or normal donors. Two VL patients with parasite converted to microscopically negative after treatment were detected positive with qPCR. The patients with bigger skin lesion in CL and higher level of immunoglobulin or splenomegaly in VL, had the higher parasite load detected by qPCR. The parasite load was significantly reduced after treatment. In conclusion, the mkDNA-based qPCR assay that we developed in this study can be used not only for diagnosis of both cutaneous and visceral leishmaniasis with high sensitivity and specificity, but also for evaluating the severity and treatment efficacy of this disease, presenting a rapid and accurate tool for clinical surveillance, treatment monitoring and the end point determination of leishmaniasis.